Evaluation of thermal couple impedance model of power modules for accurate die temperature estimation up to 200 °C. (1st May 2022) - Nakamura, Yohei; Kuroda, Naotaka; Nakahara, Ken; Shintani, Michihiro; Sato, Takashi
Abstract: This paper presents an experimental evaluation of the thermal couple impedance model of power modules (PMs), in which silicon carbide (SiC) metal-oxide-semiconductor field-effect-transistor (MOSFET) dies are implemented. The model considers the thermal cross-coupling effect, representing the temperature rise of a die due to power dissipations by the other dies in the same PM. We propose a characterization method to obtain the thermal couple impedance of the SiC MOSFET-based PMs for model accuracy. Simulations based on the proposed model accurately estimate the measured die temperature of three PMs with different die placements. The maximum error between measured and simulated die temperatures is within 8.1 °C in a wide and practical operation range from 70 °C to 200 °C. The thermal couple impedance model is helpful to design die placements of high-power PMs considering the thermal cross-coupling effect.